PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENUMBUHKAN LITERASI PADA MATA PELAJARAN IPAS DI KELAS IV DENGAN MEDIA LAP BOOK - Laili Baitu Masithoh; Ngurah Ayu Nyoman Murniati; Sutarman Sutarman; Choirul Huda (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
This study aims to foster literacy in IPAS learning outcomes with a problem-based learning model in grade IV SD Negeri Siwalan students assisted by Lap-Book media. The type of this research is classroom action research which conducted in two cycles, the subjects in this study were grade IV students totaling 28 people. The research techniques were observation, tests and documentation by using descriptive analysis. The results show that the application of the problem-based learning model assisted by Lap-Book media can foster student literacy, this can be evidenced from the recapitulation of the results of cycle I obtained an average value of 82 with a percentage of 82% while in cycle II an average value of 90 with a percentage of 100% was obtained. This proves that the use of problem-based learning models assisted by Lap-Book media can foster the literacy of fourth grade students in IPAS subjects.